Testing the General Theory of Crime with the Circumplex Model: Curvilinear Relations between Family Functioning and Self-Control. Issue 6 (2nd June 2020) - Gomes, Hugo S.; Gouveia-Pereira, Maria
ABSTRACT: The relation between family and low self-control is usually studied within linear hypotheses. In this study, we intended to test the familial origin of self-control under a curvilinear hypothesis. This is a cross-sectional study, with a sample of 448 adolescents and young adults. Data analysis was based on correlation and regression-based statistics. Results revealed linear associations between family functioning and juvenile deviant behavior, contrary to self-control which presented curvilinear relations with family cohesion and flexibility (i.e. both high and low extreme levels were associated with low self-control). This finding suggests a new approach to the familial origin of low self-control.